2019
DOI: 10.21608/ejhbmt.2019.192016
|View full text |Cite
|
Sign up to set email alerts
|

Soluble CD163 as a surrogate marker of fibrosis regression in chronic HCV patients receiving direct antiviral agents

Abstract: Background: Over 80 million people are infected globally with chronic HCV. It promotes inflammation and, hence. hepato-carcinogenesis. As a result, resolving HCV infection should result in decreased incidence of hepatocellular carcinoma. Oral DAAs introduction has changed overall prognosis of HCV. SVR has been linked to improved liver function as well as a reduction in clinical consequences and all-cause mortality. Monocytes and macrophages generate CD163, a hemoglobin scavenger receptor. In a variety of hepat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 38 publications
1
0
0
Order By: Relevance
“…In addition ,Isaac et al (2019) reported that HCV infected patients receiving successful therapy had lower levels of sCD163. Decreased levels of sCD163were associated with regression of fibrosis and disease severity [33]. From our results we can conclude that peripheral blood monocytes expressing the cognate marker CD14 was reduced in HCV patients mainly those without complications.…”
Section: E Correlation Analysissupporting
confidence: 59%
“…In addition ,Isaac et al (2019) reported that HCV infected patients receiving successful therapy had lower levels of sCD163. Decreased levels of sCD163were associated with regression of fibrosis and disease severity [33]. From our results we can conclude that peripheral blood monocytes expressing the cognate marker CD14 was reduced in HCV patients mainly those without complications.…”
Section: E Correlation Analysissupporting
confidence: 59%